Mediation: conceptual perspectives in Education and Information Science - Silva, Rovilson Jose da; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Minas Gerais, Escola Biblioteconomia, 2018)
The text approaches the mediation concept, used in the area of Education as in Information Science, in a path that goes from the epistemological aspect of the word to approximate it to the perspective of the historical materialism, dialectic, marxian that influences the work of Vygotsky (1995) and Bakhtin (1997); it also dialogues with Freire (2003) and Almeida Junior (2015), authors that have been used in the highlighted areas. In that context, the bibliographical method is used to discuss perspectives on the concept of mediating protected for the Education and for the Science of the Information, tends as support aspects of the Vygotskian theory. It is concluded that both areas have convergences and divergences that can be equalized for a better use of the mediation on behalf of reading and reader's formation in both areas.
Keywords: Mediation; Education; Information Science